2014
DOI: 10.1021/nn501138w
|View full text |Cite
|
Sign up to set email alerts
|

Gels of DNA Nanostars Never Crystallize

Abstract: Using state-of-the-art numerical techniques, we show that, upon lowering the temperature, tetravalent DNA nanostars form a thermodynamically stable, fully bonded equilibrium gel. In contrast to atomic and molecular network formers, in which the disordered liquid is always metastable with respect to some crystalline phase, we find that the DNA nanostar gel has a lower free energy than the diamond crystal structure in a wide range of concentrations. This unconventional behavior, here verified for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 50 publications
9
107
0
6
Order By: Relevance
“…40 The dynamics of both polyelectrolyte stars having inter-mediate number of arms and moderately polymer-grafted nanoparticles show sharp slowing down with increasing concentration that is symptomatic of incipient solidification. Sciortino and coworkers 105 have recently shown that nanoparticles with a moderate number of grafted DNA chains can form an equilibrium amorphous state in which the crystalline state is metastable. We expect the same situation to arise in soft star polyelectrolyte stars having a moderate number of arms.…”
Section: Discussionmentioning
confidence: 99%
“…40 The dynamics of both polyelectrolyte stars having inter-mediate number of arms and moderately polymer-grafted nanoparticles show sharp slowing down with increasing concentration that is symptomatic of incipient solidification. Sciortino and coworkers 105 have recently shown that nanoparticles with a moderate number of grafted DNA chains can form an equilibrium amorphous state in which the crystalline state is metastable. We expect the same situation to arise in soft star polyelectrolyte stars having a moderate number of arms.…”
Section: Discussionmentioning
confidence: 99%
“…191 In particular, it was shown that patchy systems combining low valence, bond flexibility and soft interactions can stabilize the liquid phase in contrast to the solid one even in the zero-temperature limit, meaning that even at extremely low temperatures the entropic term prevails over the energetic term in the free energy balance of such systems. 190 These results were found for patchy models apt to describe associating fluids or DNA-coated colloids with limited valence, but also tetravalent DNA nanostars, i.e.…”
Section: Patchy Particles From the Bottom-up Routementioning
confidence: 99%
“…extremely flexible patchy units with four bonding patches, were shown to never crystallize and form instead a thermodynamically stable, fully bonded equilibrium gel. 191 In recent years, polymer-based macromolecules or nanocomposites (such as mixtures of polymers and colloids) were shown to be extremely powerful and versatile systems for the self-assembly of soft functionalized nanoparticles. 26 Janus-like, triblock, striped and multi-patch units can indeed be created by playing with the topology, the geometry and the type of polymeric macromolecules.…”
Section: Patchy Particles From the Bottom-up Routementioning
confidence: 99%
See 1 more Smart Citation
“…This treatment is sufficient to obtain good agreement with experimental data on the structural, mechanical, and especially the thermodynamic properties of single-and double-stranded DNA. Consequently, the model has provided key insights into many different processes relevant to DNA nanotechnology [32][33][34][35][36][37][38][39][40] and biophysics [41][42][43][44][45] and importantly has also been shown to provide direct agreement with experimentally measured properties on a range of systems including DNA overstretching, 45 a two-footed DNA walker, 35 and toehold-mediated strand displacement. 39,46 Despite these achievements, there are some areas where oxDNA can be improved.…”
Section: Introductionmentioning
confidence: 99%